High-Definition 3D Stereoscopic Microscope Display System for Biomedical Applications. (19th January 2010) - Kwon, Ki-Chul; Lim, Young-Tae; Kim, Nam; Yoo, Kwan-Hee; Hong, Jong-Myeon; Park, Gi-Chang
Abstract : Biomedical research has been performed by using advanced information techniques, and micro-high-quality stereo images have been used by researchers and/or doctors for various aims in biomedical research and surgery. To visualize the stereo images, many related devices have been developed. However, the devices are difficult to learn for junior doctors and demanding to supervise for experienced surgeons. In this paper, we describe the development of a high-definition (HD) three-dimensional (3D) stereoscopic imaging display system for operating a microscope or experimenting on animals. The system consists of a stereoscopic camera part, image processing device for stereoscopic video recording, and stereoscopic display. In order to reduce eyestrain and viewer fatigue, we use a preexisting stereo microscope structure and polarized-light stereoscopic display method that does not reduce the quality of the stereo images. The developed system can overcome the discomfort of the eye piece and eyestrain caused by use over a long period of time.